Mereduksi Negatif Belief dengan Pendekatan Hipnoterapi - Nikmarijal Nikmarijal (Tarbawy : Jurnal Pendidikan Islam, 2019)
Negative beliefs are excessive and uncontrollable concerns in self-development and maintenance that can make a person feel rejected, dissatisfied and feel rejected. Hypnotherapy is applying hypothetical techniques to encourage the subconscious mind to find solutions to problems. The study used a quantitative approach with a quasi-experimental design using a pretest-posttest design model. From this study it was found that: (1) there was a significant difference between negative belief in the pretest and posttest of students in the experimental group. (2) there is no significant difference between the negative beliefs of students in the pretest and posttest in the control group. (3) there is a significant difference between the students' negative belief in the posttest of the control group and the posttest of the experimental group. So it can be concluded that negative beliefs can be reduced through a hypnotherapy approach.